MHC Class II Auto-Antigen Presentation is Unconventional - Sadegh-Nasseri, Scheherazade; Kim, AeRyon (Frontiers in Immunology, 2015)
Antigen presentation is highly critical in adoptive immunity. Only by interacting with antigens presented by MHC Class II molecules, can helper T cells be stimulated to fight infections or diseases. The degradation of a full protein into small peptide fragments bound to class II molecules is a dynamic, lengthy process consisting of many steps and chaperons. Deregulation in any step of antigen processing could lead to the development of self-reactive T cells or defective immune response to pathogens. Indeed Human Leucocyte Antigens (HLA) Class II genes are the predominant contributors to susceptibility to autoimmune diseases. Conventional antigen processing calls for internalization of extracellular antigens followed by processing and epitope selection within antigen processing subcellular compartments, enriched with all necessary accessory molecules, processing enzymes, and proper pH and denaturing conditions. However, recent data examining the temporal relationship between antigen uptakes, processing and epitope selection revealed unexpected characteristics for autoantigenic epitopes, which was not shared with antigenic epitopes from pathogens. This review provides a discussion of the relevance of these findings to the mechanisms of autoimmunity.